POTENTIAL OF HYDROGEN AND SPECIFIC GRAVITY AS UROLITHIASIS IN CATS INDICATOR - Julianta, Teresia Irene; Arjentinia, I Putu Gede Yudhi; Putriningsih, Putu Ayu Sisyawati (Buletin Veteriner Udayana, 2022)
Urolithiasis can be defined as the formation of sediment anywhere within the urinary tract. The main factor that regulates mineral crystallization and urolit formation is the degree of urine saturation with certain minerals. This study aims to determine the degree of acidity (pH) and specific gravity of urine (BJ) cats can serve as an indicator of urolithiasis incidence and know the type of urolith formed in cat urolithiasis. A total of 15 urine cat samples with urolithiasis were used in this study. Urine was tested by dipstick to observe changes in BJ and urinary pH and the examination of sediments by microscope to observe the urolith formed. The results show that the degree of acidity (pH) of urine can be used as an indicator to diagnose urolithiasis in cats, but specific gravity (BJ) of urine can not be used as an indicator to diagnose urolithiasis in cats and urolit that is formed urolit struvit and urolit calcium.